A Psycholinguistic Investigation into the Morphosyntactic ability of Gender Marking among Sequential and Simultaneous Bilinguals: A Comparative Study - Tariq, Nida (The Lighthouse Journal of Social Sciences, 2024)
With multilingualism on the rise, people in countries like Pakistan are faced with challenges pertaining to management of these languages at the same time (Rahman, 2022). Parents to the new generation are taking to inoculate early bilingualism in their children in an attempt to prepare their children for schools and to ensure maximum language-dependent academic outcome in future, since English is the modern medium of Pakistani elite education system. In this respect, the present study sought to explore an important aspect related to multilingualism i-e the co-development of morphosyntactic development of Urdu and English in such early bilinguals of Pakistan in order to analyze the correlation of a child’s age and the sequence of language acquisition with the bilingual proficiency he develops in both languages. To this end, a sample of 48 bilinguals from local schools at Islamabad comprising 24 simultaneous and 24 sequential bilinguals was constructed. Findings revealed that children with a largely gender-neutral language like English as their first language face difficulties trying to put their passive language (Urdu) into use later, since the latter is a largely morphosyntactically gendered language, whereas the case with bilinguals with Urdu as their first language is quite the opposite; it tends not to interfere with English which they learn later over the years. The reason for this is that Urdu is a heavily gendered language in terms of morphosyntax. This study may be insightful for parents who encourage the use English over Urdu among their children for better academic or social outcomes in future.